Study of spatial organization and hierarchy in the informational system of the front-of-package of gluten-free pasta: Information Design considerations - Ribeiro Jeronimo, Lucas; Rolim Miranda, Eva (InfoDesign, 2023)
Gluten restriction claims on the front of packages are especially important for those on a gluten-free diet. The objective of this work is to identify patterns and differences in the strategies of the information systems and what treatment is given to the gluten-free claim and its correlation with the other information, taking into account the spatial organization and informational hierarchy on the front panel of packages of gluten-free pasta found for convenience. We use tools from Information Design and graphic language to qualitatively analyze the packaging. Companies use different strategies in their information systems, some prioritize the gluten-free claim and others less. There is no consensus on the way the gluten restriction is written, neither in typography, nor in color, nor in the way of symbolization, nor in the area it occupies on the front panel, there’s just a tendency to center that information or keep it on the left.